“Home Away From Home”: A Critical Metaphor Analysis of Displaced Ukrainian Women’s Experiences With Their Canadian Hosts - Areej Al-Hamad; Yasin M. Yasin; Kateryna Metersky; Sepali Guruge (Global Qualitative Nursing Research)
Displaced by the Russian invasion, Ukrainian women face complex challenges in adapting to new environments. This study explores their experiences living in homestay arrangements in Canada, drawing on Conceptual Metaphor Theory and Critical Metaphor Analysis to examine how they express displacement, adaptation, and integration. Eighteen women participated through photo-elicitation interviews, metaphor-building activities using AI-generated images, and focus group discussions. The participants created metaphors to represent their hosting experiences, which were analyzed using Charteris-Black’s framework for Critical Metaphor Analysis alongside thematic narrative analysis. Metaphors such as “The Cardboard House,” “Ferris Wheel of Photos,” and “Warm Safe House” captured their resilience, vulnerability, and evolving sense of belonging. These metaphors informed three central themes: the search for stability, safety, and peace; the process of adaptation and expressions of gratitude; and the emotional dislocation tied to homeland connections. The findings highlight the emotional complexity of homestay experiences and the need for culturally sensitive, structured hosting models. For nursing, this underscores the value of trauma- and culturally-informed care to support displaced women’s psychosocial well-being.